Identifikasi Nilai Keekonomian Survey Hidrografi-Geofisika menggunakan Peralatan Multibeam Echosounder (MBES) - Edy Soesanto (Jurnal Jaring SainTek, 2023)
The Multibeam Echosounder is a tool for determining the depth of water by sweeping large areas of the seabed. The operating principle of this tool in general is based on the emission of pulses that are emitted directly towards the seabed and after that acoustic energy is reflected back from the seabed (seabel), several sound beams (beams) are electronically generated using signal processing techniques so that the beam angle is known. . Multibeam echosounder can produce high-resolution bathymetry data. The Multibeam Echosounder is characterized by the following parameters Frequency in the range 12 to 500 kHz. Sweep angle range is between +75 ͦto 85 ͦ, Accuracy generally decreases as swath width increases. The width of the sweep is 4x to 5x the water depth and the addition of the swath width depends on the depth of the survey. Using Multibeam Echosounder (MBES) acoustic equipment can improve data quality and the survey area coverage is able to obtain data coverage with a wider area, more detailed data as well as time efficiency and cost effectiveness..